Feminist Clinic in Red-ES - Bernardini, Romina; Robledo, Malena (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The network of feminist psychologists is a national civil association that has as a basis the gender perspective and feminisms in a transverse way in the conception of health, in the training of mental health professionals and in the consequent practice that is carried out . Over the years the network was expanded by different regions (Córdoba, Mendoza, La Plata) allowing the federalization of a problem that crosses the entire country, being each unique territory is its trajectories and feminist struggles. The network is created within the framework of a popular claim that goes to the streets for the struggle to expand rights and that puts on the agenda the need to cross the processes that feminities and dissidents live due to the optics of feminisms. This need dyes all aspects of life, including health. As psychologists positioned from feminisms, it is essential to think of the joints with the clinic, both the way we listen, how we intervene, from what theoretical frames we support us. Since the different theoretical frameworks in the name of psychology or mental health historically have been pathologized and criminalized identities, feelings, ethnicities, social classes. We locate it historically, but not for that reason we only refer to the past. Currently they circulate in academies, schools, faculties, offices, certain equalizations between identities, desires and psychic structures, or theoretical constructs are supported to normalize and punish desires, identities, linked modes. On many occasions the formulations of the different theoretical frameworks are repeated without asking questions to them, without historically locating them. As mental health workers it is necessary that our own ethics imply reviewing where we hear and intervene.